Increased zinc levels facilitate phenotypic detection of ceftazidime-avibactam resistance in metallo-β-lactamase-producing Gram-negative bacteria - Simon, Michaela; Gerlach, Roman G.; Pfeifer, Yvonne; Pfennigwerth, Niels; Gatermann, Sören G.; Schröder, Agnes; Hiergeist, Andreas; Hamprecht, Axel; Rügamer, Tamara; Gessner, André; Jantsch, Jonathan (Frontiers in Microbiology, 2022)
Ceftazidime-avibactam is one of the last resort antimicrobial agents for the treatment of carbapenem-resistant, Gram-negative bacteria. However, metallo-β-lactamase-producing bacteria are considered to be ceftazidime-avibactam resistant. Therefore, we evaluated a semi-automated antimicrobial susceptibility testing system regarding its capability to detect phenotypic ceftazidime-avibactam resistance in 176 carbapenem-resistant, metallo-β-lactamase-producing Enterobacterales and Pseudomonas aeruginosa isolates. Nine clinical isolates displayed ceftazidime-avibactam susceptibility in the semi-automated system and six of these isolates were susceptible by broth microdilution, too. In all nine isolates, metallo-β-lactamase-mediated hydrolytic activity was demonstrated with the EDTA-modified carbapenemase inactivation method. As zinc is known to be an important co-factor for metallo-β-lactamase activity, test media of the semi-automated antimicrobial susceptibility testing system and broth microdilution were supplemented with zinc. Thereby, the detection of phenotypic resistance was improved in the semi-automated system and in broth microdilution. Currently, ceftazidime-avibactam is not approved as treatment option for infections by metallo-β-lactamase-producing, Gram-negative bacteria. In infections caused by carbapenem-resistant Gram-negatives, we therefore recommend to check for the presence of metallo-β-lactamases before initiating ceftazidime-avibactam treatment.